Immune cell metabolic reprogramming in hepatocellular carcinoma: mechanisms, tumor microenvironment, and future immunotherapeutic directions - Zhou, Lichen; Zhang, Wenjie; Liu, Zhuoran; Xie, Yaming; Jiang, Kangyi (Frontiers in Immunology, 2026)
Hepatocellular carcinoma (HCC), the most common primary liver cancer, continues to rank among the leading causes of cancer-related death despite improvements in early detection and systemic therapies. Therapeutic advances, including immune checkpoint blockade, cancer vaccines, and adoptive cell therapies, have broadened treatment possibilities. However, their efficacy and durability are often limited by immune evasion within a metabolically challenging tumor microenvironment (TME). This review consolidates current knowledge on how metabolic reprogramming in immune cells influences HCC progression, therapy resistance, and clinical outcomes. We discuss the roles of glycolysis, oxidative phosphorylation, fatty acid oxidation, and amino acid metabolism kynurenine pathways—in regulating the differentiation and function of T cells, regulatory T cells, macrophages, dendritic cells, natural killer cells, and B cells. Environmental factors such as hypoxia, lactate accumulation, adenosine signaling, and lipid remodeling act as key TME cues that suppress antigen presentation, impair cytotoxic responses, and promote immunosuppressive myeloid phenotypes. Building on these mechanisms, current strategies focus on targeting metabolic checkpoints in immune cells, reshaping the TME, and integrating metabolic modulation with checkpoint inhibitors to enhance therapeutic efficacy. In addition, candidate biomarkers (including circulating metabolites, multi-omics profiles, and liquid-biopsy indicators of immune metabolism) offer opportunities for patient stratification and dynamic monitoring. Together, these insights provide a conceptual framework in which precise modulation of immune metabolism can potentiate existing immunotherapies and guide rational combination strategies, warranting further clinical investigation to achieve sustained benefit in HCC.